1985
DOI: 10.1111/j.1600-0536.1985.tb01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐response assessments of Kathon® biocide (I). Diagnostic use and diagnostic threshold patch testing with sensitized humans

Abstract: Nearly all effective, commercially available preservatives possess skin sensitization potential. This manuscript describes a program of diagnostic patch and practical use testing of consumer products that contained Kathon CG, a relatively new biocide. A series of threshold diagnostic patch tests demonstrated that the minimal elicitation concentration in occluded patch testing of allergic subjects considerably exceeded the concentrations of the biocide typically present in normal diluted use of the test product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…At least 1 of the test products was used at least 1X daily. No skin reactions indicative of allergic contact dermatitis elicitation were observed amongst any of the subjects (93).…”
Section: R III Se-ojfmentioning
confidence: 85%
“…At least 1 of the test products was used at least 1X daily. No skin reactions indicative of allergic contact dermatitis elicitation were observed amongst any of the subjects (93).…”
Section: R III Se-ojfmentioning
confidence: 85%
“…The typical formulation of MCI/MI into shampoo products at 5 ppm produces in-use exposure levels well below that limit. The fact that most sensitized individuals can safely use rinse-off products containing those levels of MCI/MI (12,47) indicates that this combination of in-product concentration and in-use exposure represents an acceptable formulation of this known contact allergen.…”
Section: Exposure-based Risk Assessmentmentioning
confidence: 99%
“…These products were tested as received or as diluted solutions. The LD, , rates for females were45 and 64 mg/kg a.i., while those for males were 40,41,45,50,56,57,64, and 78.5 mg/kg a.i. These are classified as moderately to highly toxic by the Hodge and Sterner system of cla~sification.…”
Section: Absorption D Istr I B Uti 0 N Metabolism a N D Excretionmentioning
confidence: 96%
“…The investigators suggested that the small and stable prevalence of MVMCI-CG sensitivity and the low rate of new sensitization were reflective of a slight potential for ~ensitization. '~~' H a n n u k~e l a '~~' reported a rapid increase in MVMCI-CG allergy in Finland (Table 10 Weaver et al (56) conducted a diagnostic provocative use test to determine the skin sensitivity of humans to consumer products containing MVMCI-CG. Eighteen subjects who had a known skin hypersensitivity to MVMCI-CG (confirmed through positive reactions to diagnostic patch testing with an aqueous solution containing 100 ppm) were given various prototype products to use in place of their regular brands for periods of three or six weeks.…”
Section: Cosmetic Ingredient Rev1 Ewmentioning
confidence: 99%